2008
DOI: 10.1007/s11605-008-0600-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Venous Thromboembolism Rates Vary Significantly After Different Types of Major Abdominal Operations

Abstract: Highest risk for VTE was associated with splenectomy, lowest risk with bariatric surgery. Since bariatric patients are known to have greater risk for this complication, these findings may reflect better awareness/prophylaxis. Further studies are necessary to quantify effect of best-practice guidelines on prevention of this costly complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 50 publications
4
53
1
Order By: Relevance
“…It is possible that the increased risk associated with splenectomy was a postoperative phenomenon that might be seen with any major abdominal operation. Because the risk for postoperative thromboembolism has been shown to vary by type of operation, 31 the site of postoperative thrombosis (ie, abdominal vs peripheral) might also vary in the early vs later postoperative period. Because AbVTE is typically thought of as a surgical complication, it is not surprising that there was a fivefold higher risk of AbVTE in the early postoperative period that did not persist.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the increased risk associated with splenectomy was a postoperative phenomenon that might be seen with any major abdominal operation. Because the risk for postoperative thromboembolism has been shown to vary by type of operation, 31 the site of postoperative thrombosis (ie, abdominal vs peripheral) might also vary in the early vs later postoperative period. Because AbVTE is typically thought of as a surgical complication, it is not surprising that there was a fivefold higher risk of AbVTE in the early postoperative period that did not persist.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is thought that mechanisms separate from reactive thrombocytosis after splenectomy may lead to a hypercoagulable state [39,40]. These findings may indicate the potential needs for anticoagulant therapy after surgery along with splenectomy [41,42] and preservation of the spleen is advantageous for reduction of thrombotic complications after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the majority of them receiving chemoprophylaxis [14,15]. This risk level, and also the risk reported by Mukherjee et al [3] would justify our use of 2% with a 1% margin as a basis or our non-inferiority test. We have found in this test that our reported rates without chemoprophylaxis is not worse than that reported in the West in patients receiving chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 68%
“…Mukherjee et al found that the incidence of VTE was 1.76% in patients undergoing hepatectomy and 2.91% in patients undergoing pancreatectomy respectively. Furthermore, the odds of developing VTE for these operations were found to be more than twice (OR 2.55 and 2.07 respectively) that of bariatric surgery patients [3]. Unfortunately, no data exists in literature on the incidence of VTE in HPB surgery patients in Asian patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation